Life Among the Great Plains Indians - Rice, Earle (San Diego, CA : Lucent Books, 1998)
Describes the everyday life of the Native Americans living on the Great Plains before the coming of the Europeans, covering their religion, social customs, government, and art.
Includes bibliographical references and index.
11 years and up
Keywords: Indians of North America -- History -- Juvenile literature. -- Great Plains; Indians of North America -- Social life and customs -- Juvenile literature. -- Great Plains; Indians of North America -- Great Plains